"Tão voltado para o futuro e tão consciente do seu passado": o Colégio Pedro II no contexto da Lei 5692/71 - Larissa Freire Pereira (2024)
This work aims to analyze the impacts of the establishment of the dictatorial regime on the Colégio Pedro ll Rio de Janeriro daily’s life. The time frame covers the year 1964, with the civil-military coup, with emphasis on the reform established by Law 5,692/71, ending in 1982, when professional education was no longer mandatory by Law No. 7,044/82. We adopted school culture as a theoretical reference, from Antonio Viñao Frago’s perspective, dialoguing with Ivor Goodson’s studies, for the discussion on the socio-historical analysis of the curriculum. To aid this problematization, we use the concepts of accommodation, resistance and adhesion, as proposed by Rodrigo Motta. The research examines four of the main newspapers circulating in Rio de Janeiro during the period, documents from the National Archives (DOPS and Projeto Memórias Reveladas), documents authored by the shcool’s head master during the period, such as textbooks and other documents published by the school’s head master, such as articles from newspapers and conferences, Law No. 5,692/71 and administrative documents internal to the school: studies carried out by the Implementation Committee of Colégio Pedro II (1976), teahcer’s meeting minutes and curricula approved in 1972 and 1977 Thus, analyzing the process of negotiations involving the school community with dictatorial governments, we identified the impasses and contradictions that were involved in a professional curriculum creation in a school with a humanistic tradition. In the first chapter, we analyzed the reference institution for the research, Colégio Pedro II, from its creation to the period studied, demonstrating its importance for public educational policies. In chapter two we analyze the two attempts to change the curriculum based on the Curriculum Reform based on Law nº 5,692/71 and, in the last chapter we analyze the subjects of the school community, students, teachers, General head master based on the tensions and conflicts that existed during the period studied. We were able to identify an institution in crisis during the period, from several aspects: the large decrease in enrolled students; the loss of prestige, due to the replacement of the humanist tradition by professional training; the impossibility of offering the desired courses, due to the lack of material and teachers, and the ambiguous relationship with the repressive processes, which occurred internally and externally to the school, and victimized students and teachers.